Testing the implementation potential of resource recovery and reuse business models: from baseline surveys to feasibility studies and business plans - Otoo, Miriam; Drechsel, Pay; Danso, George K.; Gebrezgabher, Solomie A.; Rao, Krishna; Madurangi, Ganesha (International Water Management Institute, 2016)
In many developing countries, the sanitation sector is highly subsidized by public sector agencies which has resulted in inadequate and inequitable provision of waste management services. The historical reliance on public sector provision has partly prevented the development of markets in sanitation services, including resource recovery and reuse (RRR). A paradigm shift in the sanitation sector towards cost recovery is increasingly being supported by many donors pushing for private sector participation and waste- to-wealth programs. This development advocates for a shift from waste 'treatment for disposal' to 'treatment for reuse' as the latter offers options for business development and cost recovery for the sanitation sector.